The Perspective of End-Stage Renal Disease (ESRD) Patients Undergoing Peritoneal Dialysis (PD) Toward Self-Care: Integrative ReviewThe Perspective of End-Stage Renal Disease (ESRD) Patients Undergoing Peritoneal Dialysis (PD) Toward Self-Care: Integrative - Thong-on, Rattiya; Kongvattananon, Puangpaka; Sompraserl, Chonchuen (The Bangkok Medical Journal, 2018)
To synthesize the meaning of self-care regarding peritoneal dialysis (PD) for end-stage renal disease (ESRD) patients. A systematic review and thematic analysis of qualitative studies were conducted regarding the perspectives of self-care by adults, and PD.MEDLINE, PsycINFO, and CINAHL databases were searched from January 1st, 2008 until April 1st, 2017. Seven studies involving 107 participants were included and three themes: self-control (adherence and confidence in managing PD), self-monitoring and self-management (lifestyle adaptation, managing dialysis, managing medicine and managing environment). The PD impacts on patients’ behaviors and lifestyle were identified. Self-care refers to individual actions that are associated and interact with everyday life activities for good living. Self-care involves self-monitoring, management and control of personal activities that affect health. Healthcare providers must support and educate PD patients to develop their own self-care abilities.